2022
DOI: 10.3390/ma15082797
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Acceleration Admixture Type and Composition of Cement on Hydration Heat and Setting Time of Slag Blended Cement

Abstract: This article presents recent research on cements containing GGBFS and their modifications with accelerating admixtures. The initial setting time and hydration heat evolution results are presented for cement CEM II/B-S and CEM III/A manufactured with three Portland clinkers of various phase compositions. The research was carried out at 8 °C and 20 °C. The main objective is to assess the behavior of blended cements in cooperation with modern admixtures that contain nucleation seeds. The authors aimed to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Moreover, there are reports employing C-S-H based commercial admixtures, but without stating the origin/details of such admixtures. These works cannot be reproduced and they are cited here just as examples of reporting practices that should be improved [ 54 , 55 , 56 , 57 ]. An intermediate case is the studies by Golewski and Szostak [ 58 , 59 ], where they indicated that the admixture was Master X-Seed, but the actual type was not detailed.…”
Section: C-s-h Nucleation Seedsmentioning
confidence: 99%
“…Moreover, there are reports employing C-S-H based commercial admixtures, but without stating the origin/details of such admixtures. These works cannot be reproduced and they are cited here just as examples of reporting practices that should be improved [ 54 , 55 , 56 , 57 ]. An intermediate case is the studies by Golewski and Szostak [ 58 , 59 ], where they indicated that the admixture was Master X-Seed, but the actual type was not detailed.…”
Section: C-s-h Nucleation Seedsmentioning
confidence: 99%
“…However, a recent and innovative field of research brings a technology called by C-S-H seeds as a possible solution to overcome this problem, as seen in Stephan (2018), Li, Zhang, Xu andMonteiro (2020); Pedrosa, Reales, Reis, Paiva, and Fairbairn (2020), John (2022) and Pizon, Piekarczyk & Miera (2022). Because of the low content of this additive, its environmental impact and additional cost is considered negligible (Land & Stephan, 2015;John, Epping & Stephan, 2019;Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%